Faktor-faktor yang Berhubungan dengan Keputusan Pembelian Produk Hortikultura melalui Instagram di KedaiMart - Kusumarahman, Kintami; Djuwendah, Endah (Universitas Galuh, 2024)
Developments in Information and Communication Technology (ICT), the Covid-19 Pandemic and problems with the marketing of agricultural products act as catalysts for the development of E-grocery in Indonesia. KedaiMart is here with the aim of making an impact on farmers by building an ecosystem that supports farmers to act as offtakers of crop products. KedaiMart implements a social media marketing strategy, one of which is using social media Instagram. The constraints and problems faced by KedaiMart raise the question whether using Instagram as social media marketing is related to purchase decisions made by Instagram users, especially KedaiMart followers. In this study, four indicators context, communication, collaboration and connection were used to measure KedaiMart's social media marketing relationships. Meanwhile, perception of consumers is measured using perceived usefullness, perceived ease of use, trust and perceived of price with the decision to purchase horticultural products at KedaiMart. This study uses a quantitative research design using survey methods. The purposive sampling technique was used in the sampling procedure in the study and the number of respondents was set at 140 respondents. Distribution of online questionnaires with a Likert scale of 1 to 5 was used to collect data. Furthermore, the data were analyzed using descriptive analysis tests and Chi-square tests with SPSS 26 software. According to the study's findings that there were eight factors related to the purchasing decisions of horticultural products by KedaiMart Instagram followers namely, context factors, communication, collaboration, connection, perceived usefullness, perceived ease of use, trust and perceived of price. The most highly related factors are context, communication, and collaboration.